Nonparametric Statistical Tests : A Computational Approach - Neuhauser, Markus (London : CRC, 2012)
Nonparametric Statistical Tests: A Computational Approach describes classical nonparametric tests, as well as novel and little-known methods such as the Baumgartner-Weiss-Schindler and the Cucconi tests. The book presents SAS and R programs, allowing readers to carry out the different statistical methods, such as permutation and bootstrap tests. The author considers example data sets in each chapter to illustrate methods. Numerous real-life data from various areas, including the bible, and their analyses provide for greatly diversified reading.
Included Bibliography 203-226p.; Index 227-229p.
Keywords: Bootstrap; Computer intensive methods; Nonparametric tests; Permutation tests; Statistics